Bilateral agreement for academic years 2006/2013 Lifelong Learning Programme Higher Education - Erasmus between Universidade Lusíada de Lisboa and Universidad de Málaga - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme. - Subject area: Psychology.